PENDUGAAN UMUR SIMPAN KERIPIK PISANG SALUT COKELAT “PURBARASA” KEMASAN POLIPROPILEN BERDASARKAN ANGKA TBA DENGAN METODE ASLT MODEL ARRHENIUS - Ervika Rahayu Novita Herawati; Rifa Nurhayati; Mukhamad Angwar; Vebe Wakhida (Reaktor, 2017)
Abstract SHELF LIFE ESTIMATION OF COCOA POWDER-COATED BANANA CHIPS “PURBARASA” BASED ON TBA VALUE USING ARRHENIUS MODEL OF ACCELERATED SHELF LIFE TEST (ASLT) METHOD. Cocoa powder-coated banana chips "PURBARASA" is a banana chips made from local banana in Nglanggeran Village and coated with local cocoa powder. The products are sold using polypropylene packaging with 0.08 mm thickness. The change in quality of cocoa powder-coated banana chips "PURBARASA" during storage might occur for its rancidity which is caused by fat contained in cocoa powder and absorbed oil within banana chips during deep frying processed. This deterioration can decrease its shelf life. However, the shelf life of cocoa powder-coated banana chips "PURBARASA" has not been studied yet, hence, it is really necessary to estimate shelf life of this products in order to comply with the requirements of food safety labeling on its package. The method which can be used to estimate the shelf life of cocoa powder-coated banana chips "PURBARASA" is Accelerated Shelf Life Test (ASLT) with Arrhenius model. In this case, the parameter used were based on rancidity using TBA test. Observations of deterioration carried out at three different temperatures, i.e. 35, 45 and 55oC, every 7 days for 42 days. According to the study, the estimated shelf life of cocoa powder-coated banana chips "PURBARASA" at 10, 25, 28, 300C based on TBA test were 6.2, 4.6, 4.3 and 4.2 months respectively. Kata kunci: ASLT Arrhenius; cocoa powder-coated banana chips; shelf life; TBA   Abstract Keripik pisang salut cokelat “PURBARASA” merupakan produk olahan pisang lokal Desa Nglanggeran berupa keripik yang disalut bubuk cokelat lokal, dan dikemas menggunakan kemasan polipropilen dengan ketebalan 0,08 mm. Keripik pisang salut cokelat “PURBARASA” selama penyimpanan dapat mengalami penurunan mutu berupa ketengikan yang diakibatkan oleh kandungan lemak pada bubuk cokelat dan minyak sisa hasil penggorengan deep frying yang terserap pada keripik sehingga mempengaruhi umur simpan produk. Sampai saat ini, KUBE PURBARASA belum mengetahui umur simpan produk keripik pisang salut cokelat “PURBARASA” sehingga perlu dilakukan penelitian pendugaan umur simpan produk guna memenuhi persyaratan pelabelan keamanan pangan pada kemasan produk pangan. Metode pendugaan umur simpan yang digunakan yaitu metode Accelerated Shelf Life Test (ASLT) Model Arrhenius. Parameter uji yang digunakan yaitu ketengikan berdasarkan angka TBA. Pengamatan penurunan mutu dilakukan pada tiga suhu yang berbeda yaitu suhu 350C, 450C dan 550C setiap 7 hari sekali selama 42 hari. Didapatkan estimasi umur simpan keripik pisang salut cokelat “PURBARASA” pada suhu 10, 25, 28, dan 300C berdasarkan angka TBA berturut-turut yaitu selama 6,2, 4,6, 4,3 dan 4,2 bulan. Keywords: ASLT Arrhenius; keripik pisang salut cokelat; umur simpan; TBA